The Impact of The Covid-19 Pandemic on Provincial Economic Performance in Indonesia - Rahayu, Nugroho Tulus; Muharam, Harjum (Management Analysis Journal, 2021)
The Covid-19 pandemic is a global pandemic that has a big impact to conditions of a country. However, in a country, sometimes there is a difference in the influence of the Covid-19 pandemic on one region to another. This study aims to analyze the impact of the Covid-19 pandemic on the economic performance of provinces in Indonesia. The method used in this research is the descriptive statistical method using secondary data from the Central Bureau of Statistics, related ministries, previous research, and other internet sources. The analysis found 1) the Covid-19 pandemic had a negative impact on the variables of economic growth, unemployment, poverty, and inequality; 2) The Covid-19 pandemic affected economic conditions through the implementation of large-scale social restrictions (PSBB) with the consequence of limiting the space/activities of the community so that the economic process was hampered. 3) The Covid 19 pandemic has a greater impact on provinces with high mobility and a high population, where these characteristics are mostly owned by provinces on the island of Java